THE DIFFERENCE BETWEEN COMPOUND WORDS AND WORD GROUPS - N.T.Kamoldinova (TADQIQOTLAR, 2025)
Abstract. This article examines the distinction between compound words and word  groups,  focusing  on  their  structural,  semantic,  and  grammatical  properties. Although both  involve  multiple  words,  compound  words  function  as single  lexical items,  while  word  groups  remain  syntactically  flexible.  This  study  highlights  the defining features of each, including semantic unity, orthography, stress patterns, and grammatical  behavior.  Examples  and  insights  from  morphological  and  syntactic research  help  clarify  the  differences  and  address  challenges  in  borderline  cases. Understanding  these  differences  is  essential  for  language  learners,  linguists,  and educators alike.